The Perception of English-Accented Polish –A Pilot Study - Szpyra-Kozłowska, Jolanta; Radomski, Marek (Research in Language, 2012)
While the perception of Polish-accented English by native-speakers has been studied extensively (e.g Gonet & Pietroń 2004, Scheuer 2003, Szpyra-Kozłowska 2005, in press), an opposite phenomenon, i.e. the perception of English-accented Polish by Poles has not, to our knowledge, been examined so far despite a growing number of Polish-speaking foreigners, including various celebrities, who appear in the Polish media and whose accents are often commented on and even parodied. In this paper we offer a report on a pilot study in which 60 Polish teenagers, all secondary school learners (aged 15-16) listened to and assessed several samples of foreign-accented Polish in a series of scalar judgement and open question tasks meant to examine Poles’ attitudes to English accent(s) in their native language. More specifically, we aimed at finding answers to the following research questions: • How accurately can Polish listeners identify foreign accents in Polish? • How is English-accented Polish, when compared to Polish spoken with a Russian, Spanish, French, Italian, German and Chinese accent, evaluated by Polish listeners in terms of the samples’ degree of: (a) comprehensibility (b) foreign accentedness (c) pleasantness? • What phonetic and phonological features, both segmental and prosodic, are perceived by Polish listeners as characteristic of English-accented Polish? • Can Polish listeners identify different English accents (American, English English and Scottish) in English-accented Polish? • Does familiarity with a specific foreign language facilitate the recognition and identification of that accent in foreign-accented Polish?